Integration of Root Assessment Method and Entropy Weighting in Determining Business Location Selection - Setiawansyah Setiawansyah (Journal of Artificial Intelligence and Technology Information (JAITI), 2024)
Business location is one of the key factors in determining the success of a business. Choosing the right location can affect customer accessibility, operational costs, and a company's competitiveness in the market. Determining the location of a business is often faced with various problems that can affect the success and continuity of the business. One of the main challenges is the accessibility and reach of the market, and un-strategic or hard-to-reach locations can limit customer potential and reduce business appeal. Another problem is that it often arises from the diversity of criteria that must be taken into account and the importance of each criterion varies depending on the type of business. The purpose of this study is to apply a more objective approach in determining business locations by integrating the root assessment method and entropy weighting methods in systematically evaluating various business location criteria and giving fair weight based on their level of importance. By applying this combination of methods, the decision-making process becomes more accurate and in accordance with business needs, and provides solutions that can be adapted by various types of businesses in determining strategic locations that support long-term success. Business location ranking shows the highest rated location is Location 6, with a score of 4.4254. Furthermore, Location 10 is ranked second with a score of 4.3993, followed by Location 2 in third place with a score of 4.3916. These results show that Location 6 is the most superior location in this assessment.